2016
DOI: 10.14689/ejer.2016.66.8
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation on Teacher Candidates’ Perspectives about Behaviors Positively Affecting Classroom Atmosphere

Abstract: This study investigated the impact of a Critical Friends Group (CFG), an inquiry-based professional development model, on Turkish EFL teachers. It was acknowledged that short-term workshops did not provide opportunities for teachers to make connections between the theory presented and the implications that it had for classroom teaching. CFG model accompanied with protocols was thought to be a practical and efficient way of professional development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 2 publications
0
6
0
1
Order By: Relevance
“…This study reveals that teacher candidates in classroom education department who took physical sciences education lessons during university education have some important ideas about features that teachers should have; this fact implies that awareness level of these teacher candidates is high. Bulut Ozsezer and Iflazoglu Saban [10] conducted a study that involved teacher candidates in classroom education department and they determined that participants generally know what should be done and what should be avoided in order to create a positive atmosphere in classes. Anagün, Kılıç, Atalay and Yaşar [7] made a similar research and found that teacher candidates in classroom education department mostly stated that they are sufficient for practicing Physical Sciences Education Program.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study reveals that teacher candidates in classroom education department who took physical sciences education lessons during university education have some important ideas about features that teachers should have; this fact implies that awareness level of these teacher candidates is high. Bulut Ozsezer and Iflazoglu Saban [10] conducted a study that involved teacher candidates in classroom education department and they determined that participants generally know what should be done and what should be avoided in order to create a positive atmosphere in classes. Anagün, Kılıç, Atalay and Yaşar [7] made a similar research and found that teacher candidates in classroom education department mostly stated that they are sufficient for practicing Physical Sciences Education Program.…”
Section: Resultsmentioning
confidence: 99%
“…There are various researches in Turkey about teacher candidates and their roles in classroom education; many of these researches are analyzed in terms of their contributions to science education, related results are evaluated and suggestions are made [6][7][8][9][10][11][12][13][14][15].…”
mentioning
confidence: 99%
“…In addition, it emphasizes that the teacher is an important factor in creating the classroom atmosphere. It is important that classroom has to be considered as a democratic and social system and the teacher's positive personal characteristics are highlighted (Ozsezer & Saban, 2016). The results are encouraging and suggest that teachers should involve more in design and development of web based materials to help students to learn (Akpinar & Bayramoğlu, 2008).…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…Fakta mengenai belum optimalnya kualitas ketenangan mahasiswa calon guru saat melakukan komunikasi lisan dapat berimplikasi terhadap tidak optimalnya pembelajaran yang akan dilaksanakan calon guru. Hal itu sejalan dengan laporan Ozsezer & Saban (2016) yang menjelaskan bahwa kualitas keterampilan calon guru termasuk keterampilan berkomunikasi sangat menentukan terciptanya atmosfer pembelajaran yang positif. Karena itu, rekomendasi dari penelitian ini adalah diperlukan upaya dan strategi tambahan lain dipadukan dengan penerapan perkuliahan berbasis Screencast O Matic sehingga pemberdayaan keterampilan komunikasi mahasiswa calon guru dapat semakin dioptimalkan.…”
Section: Gambar 1 Kategori Keterampilan Komunikasi Lisan Calon Guruunclassified